The Equilibrium Effects of Eviction Policies - ABRAMSON, BOAZ (Journal of Finance, 2026)
ABSTRACT I propose a dynamic equilibrium model of rental markets that endogenously gives rise to defaults on rents and evictions. In the model, eviction protections make it harder to evict delinquent renters, but higher default costs to landlords increase equilibrium rents. I quantify the model using micro data on evictions, rents, and homelessness. I find that stronger eviction protections exacerbate housing insecurity and lower welfare. The key empirical driver of this result is the persistent nature of risk underlying rent delinquencies. Rental assistance reduces housing insecurity and improves welfare because it lowers the likelihood that renters default ex ante.